2014
DOI: 10.3892/mmr.2014.1898
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine IL-6 is required in Citrobacter rodentium infection-induced intestinal Th17 responses and promotes IL-22 expression in inflammatory bowel disease

Abstract: Citrobacter rodentium (C. rodentium) infection is a widely used murine model to mimic human enteric bacteria infection and inflammatory bowel disease (IBD). In this model, interleukin (IL)‑17A plays critical roles in increasing chemokine and cytokine production in various tissues to recruit innate cells, including monocytes and neutrophils, to the local site of infection. However, the source of IL‑17A remains unclear, as the majority of cell types produce IL‑17A, including intestinal endothelium cells, innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
1
22
0
3
Order By: Relevance
“…Previous studies have shown that IL-6 is a pleiotropic cytokine involved in the cross talk between immune cells and stromal cells, activates the STAT3 signaling axis, is one of the main regulators of Th17 cell differentiation (46), and promotes IL-22 expression (24). IL-6-deficient mice showed an impaired defense against pneumococcal pneumonia (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IL-6 is a pleiotropic cytokine involved in the cross talk between immune cells and stromal cells, activates the STAT3 signaling axis, is one of the main regulators of Th17 cell differentiation (46), and promotes IL-22 expression (24). IL-6-deficient mice showed an impaired defense against pneumococcal pneumonia (47).…”
Section: Discussionmentioning
confidence: 99%
“…The role of LTβR in IBD has been previously characterized in the Citrobacter rodentium infection model of IBD mucosal inflammation. C. rodentium infection results in epithelial hyperplasia and mild to moderate inflammation of the colonic mucosa that can be used as a murine model for some aspects of IBD (33). C. rodentium infection causes RORγt + cells to synthesize lymphotoxin (LT) which binds to LTβR on epithelial cells, resulting in the release of chemokines, such as CXCL-1 and CXCL-2, that recruit pro-inflammatory neutrophils and macrophages (34, 35).…”
Section: Starting the Engine: Non-canonical Nf-κb Stimulatory Ligandsmentioning
confidence: 99%
“…Установ-лено, что возбуждение LTA и PGN Staphylococcus aureus рецептора TLR2 через MyD88/NF-κB сиг-нальный путь приводит к индукции синтеза IL-6 [60]. Взаимодействие SpA золотистого стафи-лококка с TNFR1 вызывает активацию фактора транскрипции NF-κB, а с EGFR -AP-1.…”
Section: Il-6unclassified
“…Интересно отметить, что при воспалении легких, вызванном PGN Staphylococcus aureus, вне зависимости от дозы IL-6 проявляет про-воспалительные свойства: способствует рекрутирова-нию полиморфноядерных лейкоцитов, формирова-нию абсцессов легочной ткани. У нокаутных мышей Il6 -/-активность воспалительной реакции легочной ткани не зависит от введенной дозы LTA, а характер воспаления отличается относительно низким уров-нем рекрутирования нейтрофилов [60].…”
Section: Il-6unclassified
See 1 more Smart Citation